Influência da erva mate (Ilex paraguariensis) na remodelação cardíaca em ratos wistar - Paiva, Carlos Eduardo Brochini de (2023)
Yerba mate is known for its therapeutic properties, including antioxidants, anti-inflammatory, antihypertensive, and anti-atherosclerotic effects, but concerns persist regarding the caffeine in its composition and its impact on the cardiovascular system. This study investigated the effects of yerba mate on cardiac remodeling in rats. Twenty-four male Wistar rats were divided into two groups: Control (GC), which received filtered water and a standard diet, and Yerba Mate (EM), which received room temperature filtered water with 6g of IIex paraguariensis in 100 ml/water and the same diet for 30 days. Cardiac remodeling was assessed through anatomical and histological aspects. The Shapiro-Wilk test was used to assess data normality, and unpaired t-tests or Mann Whitney were employed for group comparisons (p <0.05). The results revealed that the Yerba Mate group did not alter weight gain. Regarding cardiac remodeling, the EM group exhibited a significant reduction in the right ventricle-to-final body weight ratio. However, the normalized weight of the left ventricle and atria showed no changes. Histological analyses of the left ventricle did not reveal alterations in cardiomyocyte area or fractal dimension. Nevertheless, an increase in collagen deposition and decreased of fractal dimension were observed in the left ventricle of animals in the EM group. The 30-day consumption of yerba mate at room temperature altered cardiac remodeling.